Agreement between touch-screen and paper-based patient-reported outcomes for patients with fibromyalgia: a randomized cross-over reproducibility study. (2nd November 2015) - Wæhrens, EE; Amris, K; Bartels, EM; Christensen, R; Danneskiold-Samsøe, B; Bliddal, H; Gudbergsen, H
Abstract : Objectives: To compare data based on computerized and paper versions of health status questionnaires (HSQs) for sampling patient-reported outcomes (PROs) in patients with fibromyalgia (FM). In addition, to examine associations between patient characteristics (age, education, computer experience) and differences between versions. Finally, to evaluate the acceptability of computer-based questionnaires among patients with FM. Method: The study population comprised female patients diagnosed with FM. All patients completed six HSQs: the Fibromyalgia Impact Questionnaire (FIQ), the Major Depression Inventory (MDI), the 36-item Short Form Health Survey (SF-36), the painDETECT questionnaire (PDQ), the Coping Strategies Questionnaire (CSQ), and the Generalized Anxiety Disorder Self-Assessment Questionnaire (GAD-10), both on paper and using a touch screen. One HSQ was tested at a time in a repeated randomized cross-over design. The two versions were completed with a 5-min interval and between each HSQ the participants had a 5-min break. Means, mean differences with 95% confidence intervals (CIs), medians, median differences, and intraclass correlation coefficients (ICCs) were calculated for all HSQs, including relevant subscales. Associations between patient characteristics and differences between versions were explored using Spearman's correlation coefficients. Results: Twenty women, mean age 48.4 years, participated in the study. Except for one item, ICCs between touch-screen and paper versions of the HSQs examined indicated acceptable agreement (ICC = 0.71–0.99). Overall, mean and median differences revealed no differences between versions. No significant associations were observed for patient characteristics. None of the participants preferred paper questionnaires over computerized versions. Conclusions: The computerized HSQs using a touch screen gave comparable results to answers given on paper and were generally preferred by the participants.